2016
DOI: 10.1089/tmj.2015.0184
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Chinese m-Health Applications for Diabetes Self-Management

Abstract: Purpose: To examine the features and types of health information provided in Chinese diabetes mobile applications (apps) for patients' self-management. Materials and Methods: Through multiple rounds of screening, we identified a total of 95 relevant iOS (Apple, Cupertino, CA) and AndroidÔ (Google, Mountain View, CA) apps and examined each app's features and health information types based on each app's description in the app stores. We used a 15-feature algorithm to evaluate the apps' abilities for supporting d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…The Health Information Wants (HIW) framework suggests 7 types of information that patients typically desire in health care contexts: (1) information about the specific health condition, (2) treatment, (3) laboratory tests, (4) self-care, (5) complementary and alternative medicine (CAM), (6) psychosocial aspects, and (7) health care providers (HCPs) [ 6 - 8 ]. Empirical research using the HIW framework has shown that diabetes-related mobile apps for Mainland Chinese users offer inadequate information [ 9 ]. However, little is currently known about whether Chinese CVD mobile apps might offer a broad range of high-quality information and functions that can facilitate effective CVD self-management.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Health Information Wants (HIW) framework suggests 7 types of information that patients typically desire in health care contexts: (1) information about the specific health condition, (2) treatment, (3) laboratory tests, (4) self-care, (5) complementary and alternative medicine (CAM), (6) psychosocial aspects, and (7) health care providers (HCPs) [ 6 - 8 ]. Empirical research using the HIW framework has shown that diabetes-related mobile apps for Mainland Chinese users offer inadequate information [ 9 ]. However, little is currently known about whether Chinese CVD mobile apps might offer a broad range of high-quality information and functions that can facilitate effective CVD self-management.…”
Section: Introductionmentioning
confidence: 99%
“…Although mHealth apps have the potential to promote effective self-management and person-centered care [ 17 , 18 ], existing apps tend to provide limited types of information [ 9 ], lack information quality assurance [ 19 - 21 ], and offer inadequate functionalities [ 22 ]. These limitations may have negative impacts on mHealth app users.…”
Section: Introductionmentioning
confidence: 99%
“…Enhancing DSM has been shown to improve both treatment adherence and glycemic control (15,(33)(34)(35). Different approaches have been developed, and a range of education programs are available; furthermore, different scales are available to measure the overall quality and specific components of DSM (36)(37)(38)(39)(40).…”
mentioning
confidence: 99%
“…However, among our Chinese participants, the Internet was the least used source of information. Plausible reasons include, first, compared with the vast amount of high‐quality online information available to English speakers, much less such information is available in Chinese . Second, compared with their Western counterparts, Chinese participants may have lower levels of computer/Internet access and literacy .…”
Section: Discussionmentioning
confidence: 99%